On the Detection of Information Pollution and Violation of Copyrights in the Social Web - Baeth, Mohamed Jehad; Aktas, Mehmet (IEEE, 2015)
Social Media delivers its users a large-scale and easy-use platform, which cannot be delivered using traditional media. Social Media users face two important problems when using this platform in regard of user generated content: one is the undeterminable quality of information being published in which this information could be false and the other is the hard detection of copyright violations. This research is about different approaches to solve these problems and provide methodologies for detecting information pollution and violation of copyrights of users' shared data.
Keywords: Social Media Networks; Provenance; SOA; Information Pollution; Copyright Violation; Computer Science; Engineering